The great Filipino maritime tradition. (Makati Felta Book Sales)
Shows different kinds of boats, rafts, vessels used by Filipino traders and how they were able to explore some oceans and seas and survived. It also shows the skill and craftsmanship of Filipino shipbuilders
Keywords: Navigation -- History